Analisis Kesulitan Guru Matematika dalam Menghadapi Mathematics Learning Loss di SD Karuwisi Kota Makassar - Ramlan Mahmud; Latri Latri; Rahmawati Patta (Publikasi Pendidikan, 2024)
The research is an experimental study aimed at describing the effectiveness of the Learning Loss method in teaching two-dimensional figure material in Mathematics to class V students at SD Karuwisi in Makassar City. The population consisted of all class V students, with the experimental class being taught using the Learning Loss learning method, selected through simple random sampling. Data collection included measurements of Mathematics concept understanding, student activities during learning, and student responses to the learning materials. The data on student activities and responses were analyzed using descriptive analysis, while the data on Mathematics concept understanding were analyzed using both descriptive and inferential analysis. The results reveal that the implementation of the Learning Loss method is effective for Mathematics learning in two-dimensional figure material for class V students at SD Karuwisi Makassar City based on the following aspects: (a) the average posttest score for Mathematics concept understanding is higher than 70 (Minimum Completeness Criteria), and the average normalized gain score is greater than 0.29 (medium category); (b) the average score of student activities in each session is more than 2.49, indicating a tendency towards active engagement; and (c) the average student response score is greater than 2.5, indicating a tendency towards positive feedback. Therefore, it can be concluded that the Learning Loss learning method is effective for teaching Mathematics in two-dimensional figure material to class V students at SD Karuwisi Makassar City.